Dark day in the deep sea - Osborne, Mary Pope.; Murdocca, Sal (New York : Scholastic, 2009)
When eight-year-old Jack and his seven-year-old sister, Annie, join a group of nineteenth-century explorers aboard the H.M.S. Challenger, they learn about the ocean, solve the mystery of its fabled sea monster, and gain compassion for their fellow creatures.
Originally published: New York : Random House, 2008.
"A Merlin mission."
"With temporary tattoos!"--Cover.
Accelerated Reader/Renaissance Learning
106820
Keywords: Challenger (Ship : 1872-1876) -- Juvenile fiction; Oceanography -- Juvenile fiction; Compassion -- Juvenile fiction; Time travel -- Juvenile fiction; Magic -- Juvenile fiction; Tree houses -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Siblings -- Fiction; High interest-low vocabulary books; Fiction; Juvenile works